Factors associated with the level of knowledge of COVID-19 preventive measures in pregnant and puerpal women in two peruvian communities - Paucar Osorio, Fatima (2021)
The factors associated with the level of knowledge of the preventive measures of COVID-19 in pregnant and postpartum women from two Peruvian communities were determined. Quantitative, prospective, cross-sectional and analytical study. They worked with the entire population. The level of knowledge was measured through a previously validated instrument. Bivariate and multivariate analysis was performed, using linear regression with a 95% confidence interval. The results indicate that the 3 majority (64.7%) considered the use of rubber gloves as a preventive measure, while 33.8% considered the use of homemade masks incorrect and considered that domestic animals transmitted COVID-19. In the multivariate analysis, the level of knowledge was associated with having received information from their health center. There is a good level of knowledge about COVID-19 prevention in pregnant and postpartum women from two Peruvian communities, and that the main associated factor is having received information from their Health Center.